Continuous time system identification: a selected critical survey Part I - General view, some models and estimation methods - Khải, Ngô Minh (Journal of Computer Science and Cybernetics, 2016)
Part I and Part II of the paper refer to a critical survey on significant results available in the literature for identification of systems, linear in the present part and nonlinear in the following one. The most important trends in identification approaches to linear systems are from the development of optimal projection equations, which are argued by the complexity of numerical calculations and of practical applications. The perturbed a quasilinear and on Neuro-Fuzzy trends in representing nonlinear systems, i.e., functional series expansions of Wiener and Volterra, Modeling Robustness and structured numerical estimators are included. The limitations and applicability of the methods are discussed throughout.